The Influence Of Human Resource Competency, Performance-Based Budgeting, Accountability, And Transparency On The Financial Performance Of District Governments - Tri Karisma Ana Kurniati; Muhammad Gowon; Muhammad Ridwan (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the influence of human resource competency, performance-based budgeting, accountability, and transparency on the financial performance of sub-district governments, with a case study of all sub-district offices in East Tanjung Jabung Regency in 2024. This study uses a quantitative approach through a survey method, with primary data collection from 55 civil servant respondents in 11 sub-districts. Data analysis was carried out using validity, reliability, classical assumption tests, and multiple linear regression with the help of IBM SPSS Statistics 29. The results of the simultaneous test (F test) showed that the four independent variables together had a significant effect on the financial performance of sub-district governments (F count = 10.638 > F table = 2.56 and Sig = 0.000). Partially (t test), human resource competency had a significant positive effect (t = 3.195, Sig = 0.002), and performance-based budgeting also had a significant positive effect (t = 2.406, Sig = 0.020). Conversely, accountability (t = -2.179, Sig = 0.034) and transparency (t = -2.430, Sig = 0.018) had a significant negative effect on financial performance. This finding suggests that improving employee competency and strengthening performance-based budgeting can drive improvements in sub-district government financial performance. However, the lack of substantive implementation of accountability and transparency principles has a negative impact, indicating that both tend to remain merely administrative formalities. This study suggests the need for reformulation of accountability and transparency implementation strategies to truly promote the efficiency and effectiveness of public financial management.